2001
DOI: 10.1097/00042737-200103000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome: is the search for lactose intolerance justified?

Abstract: Use of a low lactose diet was disappointing in IBS patients with lactose malabsorption. Food intolerance was demonstrated in IBS patients with positive or negative LHBT and milk was identified as a problem in both groups. DBPCC were inconclusive. There appears to be little advantage in trying to separate patients who malabsorb lactose from others with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 29 publications
4
79
0
10
Order By: Relevance
“…[9] There is little advantage in trying to separate patients who malabsorb lactose from those with IBS. [20] Although LI symptoms were more common in IBS patients, in the absence of documented lactose malabsorption, we cannot be certain that the reported symptoms indeed are those of LI or simply those of IBS. So, a period of dairy product avoidance and/ or a test for lactose malabsorption may be beneficial in these patients. )…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[9] There is little advantage in trying to separate patients who malabsorb lactose from those with IBS. [20] Although LI symptoms were more common in IBS patients, in the absence of documented lactose malabsorption, we cannot be certain that the reported symptoms indeed are those of LI or simply those of IBS. So, a period of dairy product avoidance and/ or a test for lactose malabsorption may be beneficial in these patients. )…”
Section: Discussionmentioning
confidence: 88%
“…[19] The most likely explanation is hypersensitivity to the gut distension due to hydrogen gas produced by bacterial fermentation of unabsorbed lactose. [20,21] Another explanation may be a placebo effect. IBS patients probably look for association between food and symptoms and are aware of the association between lactose ingestion and symptoms of bloating, ß atulence and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Ledochowski et al [24] , which has shown that dietary changes in patients with fructose malabsorption have a beneficial effect on gastrointestinal complaints and also on mood, as documented by improvements in depression score, has already been mentioned above. However, there are also contradictory data that show that only avoiding one sugar (with proven malabsorption) may not be sufficient for patients with irritable bowel syndrome [43,44] . The phenomenon that patients with non-specific abdominal complaints frequently report improvement in their symptoms for several weeks after colonoscopy (thought to be due to bowel preparation with cleansing of the colon) underlines the possible role of bacteria in the colon.…”
Section: Therapymentioning
confidence: 99%
“…We excluded, in our study, pts with a diagnosis of SIBO because it is well described in the literature [18] that during bacterial overgrowth, subjects may have lactose intolerance not by enzyme deficiency but to premature exposure of lactose to bacteria in the small bowel before there is time for a correct absorption [19][20][21][22]. This was further validated by Nucera et al, who demonstrated in 98 subjects with IBS that small intestinal bacterial overgrowth eradication, as confirmed by negative lactulose breath test, caused a significant reduction in lactose breath test positivity [23].…”
Section: Discussionmentioning
confidence: 99%